Aporphine and bisaporphine alkaloids from Aristolochia lagesiana var. intermedia - Ferreira, Marcia L. R. [UNESP]; de Pascoli, Inara C. [UNESP]; Nascimento, Isabele Rodrigues [UNESP]; Zukerman-Schpector, Julio; Lopes, Lucia Maria Xavier [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Corydines, isocorydines, and analogous aporphine alkaloids were isolated from the leaves of Aristolochia lagesiana var intermedia, together with three bisaporphine salts (lagesianines B-D) Their structures were determined by chemical derivatizations and spectroscopic analyses Lagesianines B and C are the first examples of N-CH(2)-N' and C-2-O-C-1' linked dimeric aporphine alkaloids, respectively, while the monomeric units of lagesianine D. which has a carbon skeleton, are linked through C-7-C-5' via ail ethane-1,2-diol group (C-7-CHOHCHOH-C-5') (C) 2009 Elsevier Ltd. All rights reserved
Keywords: Aristolochia lagesiana var. intermedia; Aristolochiaceae; Alkaloids; Aporphine; Bisaporphine; Alkaloid dimer; Lagesianines; Corydine; Isocorydine; Corydine; N alpha-oxide